The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/hed.24697
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided interstitial high-dose-rate brachytherapy in the treatment of inoperable recurrent head and neck malignancies: An effective option of reirradiation

Abstract: In patients with inoperable recurrent head and neck cancer, CT-guided interstitial HDR brachytherapy can play a role in providing palliation and tumor control. © 2017 Wiley Periodicals, Inc. Head Neck 39: E61-E68, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…There are few previous reports on the use of HDR brachytherapy as palliative treatment for head and neck cancer [ 6 , 7 , 8 ]. Skowronek et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few previous reports on the use of HDR brachytherapy as palliative treatment for head and neck cancer [ 6 , 7 , 8 ]. Skowronek et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are few previous reports on the use of HDR brachytherapy as palliative treatment for head and neck cancer [6,7,8]. Skowronek et al reported the results of palliative HDR and pulsed-dose-rate (PDR) brachytherapy in 47 cases, with a relapse of head and neck cancer [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the development of imaging modalities, such as computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography, image-based HDR BT has been implemented. Using three-dimensional (3D) cross-sectional image sets, radiation oncologists and medical physicists can depict the target volume and critical structures, and calculate the volumetric doses delivered to these organs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In the gynecological region, there are recommendations about image-based BT, where authors referring to concepts and terms in 3D image-based treatment planning, 3D dose volume parameters, aspects of 3D image-based anatomy, radiation physics and radiobiology [ 13 , 14 ].…”
Section: Purposementioning
confidence: 99%
“…The enlarged lymph nodes are mainly located in the deep upper cervical lymph node group in the upper neck. It then starts to be unilateral, and then develops to bilateral, and can spread to the middle and lower parts of the neck, and even aggravate the condition (Tselis et al, 2017;Wu et al, 2016). Therefore, it is necessary to diagnose and treat the lymph node metastasis of NPC as early as possible.…”
Section: Introductionmentioning
confidence: 99%